2016
DOI: 10.1038/srep21248
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric coupling between proximal C-terminus and selectivity filter is facilitated by the movement of transmembrane segment 4 in TREK-2 channel

Abstract: TREK-2, a member of two-pore-domain potassium channel family, regulates cellular excitability in response to diverse stimuli. However, how such stimuli control channel function remains unclear. Here, by characterizing the responses of cytosolic proximal C-terminus deletant (ΔpCt) and transmembrane segment 4 (M4)-glycine hinge mutant (G312A) to 2-Aminoethoxydiphenyl borate (2-APB), an activator of TREK-2, we show that the transduction initiated from pCt domain is allosterically coupled with the conformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…Perhaps surprisingly, 2-APB effects were not dependent on extracellular K 1 concentration. Zhuo et al (2016) interpreted their results in terms of an allosteric coupling of stimuli sensed at intracellular portions of the channel structure and gating at the SF, which supports the hypothesis of SF activation or inactivation as the sole mode of K 2P channel gating.…”
Section: An All-encompassing Role For the Selectivitysupporting
confidence: 64%
See 1 more Smart Citation
“…Perhaps surprisingly, 2-APB effects were not dependent on extracellular K 1 concentration. Zhuo et al (2016) interpreted their results in terms of an allosteric coupling of stimuli sensed at intracellular portions of the channel structure and gating at the SF, which supports the hypothesis of SF activation or inactivation as the sole mode of K 2P channel gating.…”
Section: An All-encompassing Role For the Selectivitysupporting
confidence: 64%
“…Recent work by Zhuo et al (2016) has addressed the gating mechanism for activation of TREK-2 by 2-aminoethoxydiphenyl borate (2-APB). The 2-APB site of action is a proximal portion of the C terminus (pCt) that, when deleted, as in mutant DpCt, leads to a loss of 2-APB-induced activity.…”
Section: An All-encompassing Role For the Selectivitymentioning
confidence: 99%
“…An allosteric coupling between pCt and the selectivity filter (SF) has been described in TREK2. A movement of M4 facilitates this coupling ( Zhuo et al, 2016 ). To investigate the possibility that coupling is necessary for pCt action in TREK1 and TRAAK, we modified the M4/pCt junction by replacing residues 292 to 294 by glycines in TREK1 to produce TREK1-3G, and residues 253 to 255 in TRAAK to produce TRAAK-3G.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have demonstrated that 2-Aminoethoxydiphenyl borate (2-APB), a membrane-permeable compound, stimulates the activity of TREK-2 via acting on its cytosolic proximal C-terminus (pCt; Zhuo et al, 2015a ), and opens the pore regardless of the original conformation of SF gate (Zhuo et al, 2016 ). This allosteric transduction (named as “2-APB pathway”) is initiated from cytosolic Ct and propagated to SF gate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, changes of extracelluar pH (ΔpH o ) induce the conformational transition of SF gate in K2Ps via an external sensor (Clarke et al, 2008 ; Cohen et al, 2008 ; Stansfeld et al, 2008 ; Niemeyer et al, 2010 ; Ma et al, 2011 ; Zúñiga et al, 2011 ), including TREK-2 (Sandoz et al, 2009 ; Zhuo et al, 2015a ). Such transition in TREK-2 is also facilitated by the pCt domain in TREK-2 (Zhuo et al, 2016 ). This transmission is evoked by the charge change of sensor and propagated such stimuli to SF gate, and ultimately to intracellular pCt domain, a process called as “pH o pathway”.…”
Section: Introductionmentioning
confidence: 99%